Emerging Intercalation Cathode Materials for Multivalent Metal‐Ion Batteries: Status and Challenges. Issue 11 (1st October 2021) - Chen, Susu; Zhao, Dong; Chen, Long; Liu, Guangrong; Ding, Yan; Cao, Yuliang; Chen, Zhongxue
Abstract : Multivalent metal‐ion (Mg 2+, Zn 2+, Ca 2+, Al 3+ ) batteries emerge as promising alternatives to current lithium‐ion batteries (LIBs) for grid‐scale energy storage applications because of their high safety and low cost. The bright prospect of these batteries encourages increasing research interests in recent years, hence inspirational achievements have been made over the years. Like in LIB, cathode is the most important component that determines the performance of multivalent metal‐ion batteries. Nevertheless, the development of cathode materials still faces realistic challenges, including sluggish solid‐state diffusion and slow desolvation process at the cathode/electrolyte interface. Herein, recent progresses in intercalation cathode materials for multivalent metal‐ion batteries, including vanadium and manganese oxides and their derivatives, chalcogenides, polyanions frameworks, carbon materials, MOFs (or COFs) and Mxenes are summarized. The discussions focus on the rational design and engineering of structure, morphology, and surface texture of these cathodes with the aim of revealing the material design principles for multivalent metal‐ion storage. We hope this critical review will provide the readers with a clear understanding of current status and future research directions of intercalation cathodes for multivalent metal‐ion batteries. Abstract : Multivalent metal‐ion batteries are promising alternatives to lithium‐ion batteries for grid‐scale energy storage applications because of their low cost and high safety. Nevertheless, the development of intercalation cathode materials still faces realistic challenges including sluggish solid‐state diffusion and slow desolvation process at the cathode/electrolyte interface. Therefore, in‐depth theoretical study, rational design, and engineering are crucial for searching reliable intercalation cathodes.